2018
DOI: 10.18646/2056.54.18-014
|View full text |Cite
|
Sign up to set email alerts
|

Using LEGO® To Understand Emotion Work In Doctoral Education

Abstract: In this paper, we present a project of the University of Kent Graduate School that utilises this paradox of playfulness and creativity. LEGO ® is used in workshops to explore doctoral students' emotions around the complex and solitary experience of a PhD research. We argue LEGO ® is uniquely generative for exploring emotion work. After a brief overview of the background and context to the doctoral training workshop, we provide a brief review of emotion work. We then describe the LEGO ® workshop we developed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Across the interviews, our criminological researchers described performing emotional labour in the field while carrying out their doctoral research. All of our researchers commented on the overall 'emotionfulness' of undertaking doctoral research (Baptista, 2014;Morrison-Saunders et al, 2010), and identified the need to engage in emotional labour during their PhD studies (Aitchinson and Mowbray, 2013;Brown and Collins (2018). While a number of themes were identified in the analysis, those discussed here have been highlighted as being particularly pertinent to the PhD experience.…”
Section: Findings and Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Across the interviews, our criminological researchers described performing emotional labour in the field while carrying out their doctoral research. All of our researchers commented on the overall 'emotionfulness' of undertaking doctoral research (Baptista, 2014;Morrison-Saunders et al, 2010), and identified the need to engage in emotional labour during their PhD studies (Aitchinson and Mowbray, 2013;Brown and Collins (2018). While a number of themes were identified in the analysis, those discussed here have been highlighted as being particularly pertinent to the PhD experience.…”
Section: Findings and Discussionmentioning
confidence: 83%
“…Skakni (2018) maintains that students are expected to be autonomous, but also align their practice with the norms and informal rules of the community of practice they find themselves in. Therefore, as suggested by Brown and Collins (2018 citing Beeler, 1991; Golde, 2005: 202), doctoral students characterise their identity as ‘liminal’, and this seems to be reflected in the emotional labour they perform. It can be seen from these extracts that while there is a clear understanding that emotional labour is required in the field when undertaking doctoral research, exactly what is expected, for example, in terms of the empathy or sympathy to be displayed is often not clear to our participants.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Based within an interpretivist approach that focuses on how participants create meanings (Ritchie et al, 2014, p. 12), the three studies discussed here focused on participants' PhD journeys. The first study explored emotional dissonance within the PhD and data was collected from workshops and from interviews (N. Brown & Collins, 2018;Collins & Brown, 2020). The second study looked at the transition into UK higher education by International and EU Graduate Teaching Assistants (Collins, 2019;Collins, 2021) and again collected data from workshops and interviews.…”
Section: Methodology Research Approachmentioning
confidence: 99%
“…Using the lenses of identity work and 'doctoral capital', data from three qualitative studies amongst 30 PhD students is explored to highlight the desire for validation within their PhD journeys. These studies looked at the journeys that PhD students make (two focusing on PhD students, the other on international Graduate Teaching Assistants transitioning into the UK) (N. Brown & Collins, 2018;Collins, 2019;Collins, 2021;Collins & Brown, 2020). (Here, in the UK context, it should be noted that 'International' designates PhD students from both inside and outside of the EEA, a definition recently altered, along with fee status).…”
Section: Introductionmentioning
confidence: 99%
“…This is an issue highlighted by a recent Advance HE workshop (Hanesworth 2018). Moreover, Brown & Collins (2018), inspired by contemplative pedagogies, used LEGO to support the wellbeing of researchers and acknowledged this creative approach to student wellbeing.…”
Section: Multisensory Techniques: Lego Serious Play and Reframingmentioning
confidence: 99%